Visualizing Spatial Disparities in Indonesia’s Rice Productivity Using Interactive Dashboard - Anggrayana, Willy Septian (Dinasti International Journal of Management Science, 2025)
The rice sector in Indonesia is crucial to food security, livelihoods, and socio-economic stability, as rice is the main staple food. Rice productivity (yield) in Indonesia shows significant variation across districts and cities, underscoring the need to optimize yields. However, visual analytics at this level and topic, using BPS data, is still limited. This research shows that descriptive visualization of spatial disparities in yield and structural characteristics can be approached analytically using a dashboard.  The analysis relies entirely on aggregate data at the Province and District/city levels from Sensus Pertanian BPS 2023 and the Disaster Risk Index (Inarisk) BNPB, which include 514 districts/cities and cover farm structure, farm practices, access to services, and demographics. This interactive dashboard is designed to facilitate exploration of visual distributions of productivity. The result shows various patterns of spatial and structural. This finding is actually an initial exploration. The dashboard serves as a practice for stakeholders to identify special provinces or districts/cities for further analysis, compare among districts, or formulate priorities for further analysis. This research is part of support for planning and decision-making based on data-driven approaches in the agricultural sector.